2010
DOI: 10.1002/pds.2068
|View full text |Cite
|
Sign up to set email alerts
|

Risks of congenital malformations and perinatal events among infants exposed to calcium channel and beta‐blockers during pregnancy

Abstract: Purpose Calcium channel blockers and beta-blockers are widely used during pregnancy, but data on their safety for the developing infant is scarce. We used population-based data from 5 HMOs to study risks for perinatal complications and congenital defects among infants exposed in-utero. Methods We studied women older than 15 years delivering an infant between 1/1/96 to 12/31/00, who had been continuously enrolled with prescription drug coverage for >= one year prior to delivery. Information on prescription dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 32 publications
1
82
1
1
Order By: Relevance
“…25 Although data from RCTs on the risk of neonatal hypoglycemia associated with β blockers is inconclusive, with a wide CI in the pooled estimate (RR, 0.81; 95% CI, 0.44-1.49) and unclear exposure status for the participant around the time of delivery, 25 a recent observational study reported a threefold increased risk in association with third-trimester exposure (RR, 3.1; 95% CI, 2.2-4.2). 11 These findings have physiologic plausibility, because β blockers are known to cross the placenta and have the potential to cause sympathetic blockade in exposed infants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…25 Although data from RCTs on the risk of neonatal hypoglycemia associated with β blockers is inconclusive, with a wide CI in the pooled estimate (RR, 0.81; 95% CI, 0.44-1.49) and unclear exposure status for the participant around the time of delivery, 25 a recent observational study reported a threefold increased risk in association with third-trimester exposure (RR, 3.1; 95% CI, 2.2-4.2). 11 These findings have physiologic plausibility, because β blockers are known to cross the placenta and have the potential to cause sympathetic blockade in exposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although generally considered safe for use in pregnancy, β blockers can cross the placenta and have the potential to cause physiologic changes in neonates exposed in utero. 11 Sympathetic blockade in the exposed neonates leads to 2 potential risks after delivery, neonatal hypoglycemia and neonatal bradycardia, and previous studies have suggested an association between late pregnancy β blocker exposure and these outcomes. 7,11 The magnitude of these risks and how they may vary as a function of type of β blocker remain poorly defined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of intravenous labetalol close to delivery has been associated with a few cases of neonatal bradycardia, hypotonia, respiratory distress, hypoglycaemia, circulatory collapse and feeding problems [110,111]. For severe hypertension, intravenous labetalol has been observed to produce less maternal symptoms such as hypotension, palpitations and tachycardia than intravenous hydralazine but is more associated with foetal bradycardia [112,113].…”
Section: Intravenous Antihypertensives For Acute Crisismentioning
confidence: 98%